2011
DOI: 10.1603/en11063
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Enemy Release During Range Expansion of an Evergreen Tree in Northern Europe

Abstract: Plant distributions are dynamic but the role of plant-insect interactions in controlling range dynamics is not well understood. Enemy release, for example could facilitate plant range expansion under climate change. We conducted a transplant experiment with the evergreen tree Ilex aquifolium L. in both the historical and the expanding range in Denmark to study possible effects of geographical position, small-scale distance, and plant types on presence and performance of the monophagous insect leaf-miner Phytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…, Lakeman‐Fraser and Ewers ), although this result is not universal (e.g., Skou et al. ). Combined with the results of Brown and Vellend (), our results have some important implications for understanding potential responses of species distributions to climate warming, as described in the following paragraphs.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…, Lakeman‐Fraser and Ewers ), although this result is not universal (e.g., Skou et al. ). Combined with the results of Brown and Vellend (), our results have some important implications for understanding potential responses of species distributions to climate warming, as described in the following paragraphs.…”
Section: Discussionsupporting
confidence: 73%
“…, Lakeman‐Fraser and Ewers ), while others find no such effect (e.g., Skou et al. ). However, we cannot draw generalizations at present given that so few empirical studies have tested how non‐climatic factors influence the leading edge of natural species ranges (HilleRisLambers et al.…”
Section: Introductionmentioning
confidence: 93%
“…In order to conduct a statistically valid analysis with power sufficient enough to detect significant differences in metabolic features associated with environmental and geographic variation and address low sampling numbers, we use the two‐step model proposed by Skou, Markussen, Sigsgaard, and Kollmann (2011) (see also Thiele & Markussen, 2012). The two‐step model includes a log‐normal model and a binary model and is well suited to address metabolomic data where all observations are non‐negative, but a substantial portion of the observations are zero values, as a result of many metabolic features being not present or below the detection limit.…”
Section: Methodsmentioning
confidence: 99%
“…Skou et al. (2011) did not baptize their model, but for future reference we suggest that this model is called the conditional log‐normal model . A log‐normal model often fits well for strictly positive observations, and the conditional log‐normal model is an extension that allows for zero observations that also occur frequently in ecological datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Some tests have confirmed it only partially [25][26][27], have proved negative (e.g., [28][29][30]), or have led to conclusions contradicting it [31][32][33]. A review of the results of ERH tests [34] indicated that for alien plant species the hypothesis was confirmed in about 57% of experimental studies.…”
Section: Introductionmentioning
confidence: 99%